PERJANJIAN KERJASAMA ANTARA SOFEEA WEDDING ORGANIZER DENGAN PIHAK KLIEN. STUDI KASUS: Perjanjian Kerjasama antara Sofeea Wedding Organizer dengan Farid Darmawan dan Aci Nur Azizah - Syifausy Syafiyah Rafti (2022)
This study discusses the implementation of the cooperation for the completeness of the wedding reception, with the aim of knowing the implementation of the cooperation agreement between the wedding organizer and the client and knowing the responsibility of the first party if there is a change in the implementation of the cooperation agreement that occurs between the tenant and the renting party. This research uses a normative legal approach that relies on laws and regulations or norms that are binding on human behavior. The data collection method is carried out using a case approach that is currently occurring in the community by reviewing the sharing of literature and laws and regulations. The type of data used is secondary data consisting of primary legal sources and secondary legal sources. In data collection techniques, researchers choose to conduct interviews as well as documentation. This study shows that the implementation of cooperation agreements is carried out in two types, namely in writing and orally. The form of responsibility carried out by Sofeea wedding orginizer is to refund 10% of the agreed fee in accordance with the agreement of both parties. Keywords: Agreement, Cooperation, Responsibility